An improved cell for in-situ electrochemical ESR - Compton, R; Waller, A (1985)
An improved cell for simultaneous electrochemical ESR based on a coaxial cylindrical cavity is described and shown to have high sensitivity whilst behaving as a satisfactory hydrodynamic electrode as evidenced by Tafel analysis, by Levich analysis and comparison with theory for the dependence of the ESR signal on electrode currents and electrolyte flow rate.